Fast lithium ion transport in solid polymer electrolytes from polysulfide-bridged copolymers. (September 2020) - Sun, Chengguo; Wang, Zhenxing; Yin, Lichang; Xu, Shengjun; Ghazi, Zahid Ali; Shi, Ying; An, Baigang; Sun, Zhenhua; Cheng, Hui-Ming; Li, Feng
Abstract: Solid polymer electrolytes (SPEs) are being intensively pursued as a means to develop safe, stable and long-life Li-ion batteries. However, the low Li + conductivity and transference number in SPEs still impede all-solid-state polymer batteries from practical commercialization. Here, lithium polysulfides that cause a shuttle effect problem in Li–S batteries are reduced on a Poly(ethylene oxide) (PEO) chain as an effective way to stimulate Li + transport. It is shown that the product of the reduction (main –S4 Li) dramatically increases Li + transport while forming a strong interaction with the PEO matrix through intermolecular interactions. In contrast to PEO electrolytes, the –S4 Li grafted electrolyte membranes have a lithium transfer number almost 3 times higher, and the LiFePO4 |ScPEO|Li cell shows an ultra-long cycle life exceeding 1200 cycles with a capacity decay of 0.024% per cycle at 1 C. The results reveal lithium polysulfides tremendous potential in a solid-state electrolyte system for improving the ion transport and cycling stability. Graphical abstract: Lithium polysulfides grafted on a polyethylene oxide (PEO) chain is obtained through in situ reduction of polysulfide-bridged copolymer in solid polymer electrolyte. The -S4 Li dramatically increases Li + transport while forming a strong interaction with the PEO matrix through intermolecular interactions, which also achieves the stable and intimate electrode-electrolyte interface in the cell. Image 1 Highlights: Lithium polysulfides are reduced on a PEO chain as an effective way to stimulate Li + transport. The RS4 Li grafted on PEO electrolytes have a high ionic conductivity of 2.13*10 −4 S/cm at 50 °C. The RS4 Li can form strong interaction with PEO matrix and loosen O–Li + coordination. The organic lithium polysulfide is a very attractive material for solid-state electrolytes.